Strategi Pengelolaan Sampah Berbasis Lingkungan di Kabupaten Musi Rawas - Teddy Laszuardy; Vera Surtia Bachtiar; Ummi Jayanti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Solid waste management in Musi Rawas Regency faces increasingly complex operational, spatial, and environmental challenges. The main problems are not limited to the amount of waste transported to the landfill, but also include limited service coverage, insufficient fleet capacity, incomplete intermediate treatment facilities, weak source separation, and the high dependence on Gegas landfill/final processing facility as the dominant downstream infrastructure. This study aimed to describe the existing solid waste management system, identify the major technical and governance constraints, and formulate an environmental-based strategy that is consistent with the territorial characteristics, service capacity, and local waste generation pattern of Musi Rawas Regency. A descriptive qualitative case-study approach was applied through semi-structured interviews, field observation, and document review. The results show that collected waste under normal conditions ranged from 19 to 21 tons per day and increased to approximately 25 tons per day during Ramadan due to seasonal consumption and organic waste from temporary trading activities. Waste services were supported by seven dump trucks for seven service areas, indicating that a substantial part of the regency had not been covered by formal collection services. Meanwhile, the potential waste generation based on population data reached 288.25 tons per day, showing a wide gap between transported waste and estimated total generation. The proposed strategy emphasizes waste data strengthening, service zoning, route and trip optimization, TPS/TPS3R revitalization, organic waste treatment, landfill risk control, operational standard procedures, and performance-based financing. These interventions are expected to improve service efficiency, reduce landfill burden, minimize environmental risk, and support more adaptive and sustainable local waste governance.